Lignin: green modifier for road pavement / Shahreena Melati Rhasbudin Shah, Husna Nabilah Che Husin and Tey Li Sian - Rhasbudin Shah, Shahreena Melati; Che Husin, Husna Nabilah; Tey, Li Sian (College of Built Environment, 2023)
Bitumen is a petroleum-based hydrocarbon, obtained from a crude petroleum distillation, has been widely used as a binding material in pavement construction.